Consumer Behaviour In Purchasing Of The Online Agricultural Products - Widya Fitriana; Zednita Azriani; Rika Hariance (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
This study aims to analyze the factors that influence consumer purchasing agricultural products online. .We observed three West Sumatra cities with internet access above the provincial average. Suspected individual, socio-demographic and cultural factors influence agricultural consumer behavior. This study surveyed 100 respondents by accident in the three cities. Data analysis was carried out using a logit analysis approach. The results showed that individual factors significantly affected consumer behavior while demographic and cultural factors had no considerable impact. Consumers who have regular incomes and fixed jobs have substantial opportunities to purchase agricultural products online because they are considered more effective and provide a lot of convenience during their busy activities.